2017
DOI: 10.2495/sdp-v12-n8-1299-1311
|View full text |Cite
|
Sign up to set email alerts
|

projected changes in temperature and precipitation in Sarawak state of Malaysia for selected CMIP5 climate scenarios

Abstract: This article explores the projected changes in precipitation, maximum temperature (T max) and minimum temperature (T min) in the Malaysian state of Sarawak under Representative Concentration Pathways (RCPs) with the CanESM2 Global Circulation Model. The Statistical Downscaling Model (SDSM) was used to downscale these climate variables at three stations in Sarawak. The model performed well during the validation period and thus was used for future projections under three RCPs with the CanESM2 General Circulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 19 publications
1
7
0
2
Order By: Relevance
“…The predictors that showed the best correlations with precipitation as predictand are related mostly with wind speed, geopotential, as well as high and relative humidity. This agrees with other studies using statistical downscaling methods (e.g., Hussain et al 2017;Saraf and Regulwar 2016). A bias correction was not applied to the global climate data because it was found that bias correction methods might impair the advantages of circulation models by altering spatiotemporal field consistency, relations among variables, and by violating conservation principles.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The predictors that showed the best correlations with precipitation as predictand are related mostly with wind speed, geopotential, as well as high and relative humidity. This agrees with other studies using statistical downscaling methods (e.g., Hussain et al 2017;Saraf and Regulwar 2016). A bias correction was not applied to the global climate data because it was found that bias correction methods might impair the advantages of circulation models by altering spatiotemporal field consistency, relations among variables, and by violating conservation principles.…”
Section: Discussionsupporting
confidence: 87%
“…The results presented in Table 2 show an increase of both maximum and minimum temperature over the next decades as well as a decrease in relative humidity with a slight change of precipitation which will most likely decrease for most of the considered stations-especially in the last decades of the XXI century. In contrast to the case of temperature, difficulties to perform accurately a downscaling of daily precipitation agrees with the results of other studies (Huang et al 2011;Nguyen et al 2006;i.a., González-Rojí et al 2019;Saraf and Regulwar 2016;Ahmadi et al 2014;Saddique et al 2019;Hussain et al 2017;Cavazos and Hewitson 2005;Fiseha et al 2012;Osma et al 2015), also in these studies a low correlation in a regional scale between daily precipitation and different set of predictors was found, this creates a difficulty to adjust the model and calibrate it more accurately. That can be seen in this study in the Figs.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In studies like the one performed by Nakaegawa [40] or Ospina [41], river discharge in the north of Colombia was analyzed using direct output from a GCM as a hydrometeorological input of the model, and similar studies could be performed in the four selected water districts at the east of Colombia considering the results of the current study in order to use the historical records from these areas to develop a regional climate downscaling or water budget analysis. The spatial and temporal data resolutions show acceptable characteristics for the purpose of performing reliable posterior analysis such as some developed through statistical regional downscaling on other areas with similar characteristics [31,32,[42][43][44], or water budget analysis [45][46][47][48][49]. The use of a dynamical downscaling method could also provide more accurate results, but this approach demands much more intensive computational resources and require large volumes of data which are not available for the studied regions, thus, using a statistical downscaling technique is recommended as a first approach.…”
Section: Discussionmentioning
confidence: 99%
“…The country Malaysia is located at a strategic location between the Indian and Pacific Ocean. Due to the increase in global temperature, Malaysia in both Semenanjung and Borneo is witnessing higher precipitation during their wet seasons [29,30]. Most of the flood that occur are due to natural causes such as cyclical monsoon, which results to heavy rainfall during the months of October to March [31].…”
Section: Causes Of Flooding In Malaysiamentioning
confidence: 99%